Chemodiversity of Soil Dissolved Organic Matter and Its Association With Soil Microbial Communities Along a Chronosequence of Chinese Fir Monoculture Plantations - Li, Ying; Heal, Kate; Wang, Shuzhen; Cao, Sheng; Zhou, Chuifan (Frontiers in Microbiology, 2021)
The total dissolved organic matter (DOM) content of soil changes after vegetation transformation but the diversity of the underlying chemical composition has not been explored in detail. Characterizing the molecular diversity of DOM and its fate enables a better understanding of the soil quality of monoculture forest plantations. This study characterized the chemodiversity of soil DOM, assessed the variation of the soil microbial community composition, and identified specific linkages between DOM molecules and microbial community composition in soil samples from a 100-year chronosequence of Chinese fir monoculture plantations. With increasing plantation age, soil total carbon and dissolved organic carbon first decreased and then increased, while soil nutrients such as available potassium and phosphorus and total nitrogen, potassium and phosphorus, increased significantly. Lignin/carboxylic rich alicyclic molecules (CRAM)-like structures accounted for the largest proportion of DOM, while aliphatic/proteins and carbohydrates showed a decreasing trend along the chronosequence. DOM high in H/C (such as lipids and aliphatic/proteins) degraded preferentially, while low H/C DOM (such as lignin/CRAM-like structures and tannins) showed recalcitrance during stand development. Soil bacterial richness and diversity increased significantly as stand age increased, while soil fungal diversity tended to increase during early stand development and then decrease. The soil microbial community had a complex connectivity and strong interaction with DOM during stand development. Most bacterial phyla, such as Acidobacteria, Chloroflexi, and Firmicutes, were very significantly and positively correlated with DOM molecules. However, Verrucomicrobia and almost all fungi, such as Basidiomycota and Ascomycota, were significantly negatively correlated with DOM molecules. Overall, the community of soil microorganisms interacted closely with the compositional variability of DOM in the monoculture plantations investigated, both by producing and consuming DOM. This suggests that DOM is not intrinsically recalcitrant but instead persists in soils as a result of simultaneous consumption, transformation and formation by soil microorganisms with extended stand ages of Chinese fir plantations.